Faktor yang Mempengaruhi Keputusan Pembelian Rumah Subsale bagi Pembeli Rumah di Pasir Gudang, Johor - Rosli, Hanis Najwa; Masram, Haidaliza; MD YASSIN, AZLINA; Shafii, Haryati (Research in Management of Technology and Business, 2025)
Sub sale homes refer to residential properties resold by their original owners, while new launch houses are marketed and regulated by property developers. In Johor, demand for sub-sale houses has shown positive growth, whereas demand for new launch properties has declined, contributing to an oversupply issue. Transaction data indicates that this oversupply is partly due to stronger buyer preference for sub-sale homes. Arguments on the most significant and dominant factor influencing the purchase decisions of sub-sale houses could serve as a valuable reference for property players. This study aims to identify the key factors influencing the selection of sub-sale houses among homebuyers in Pasir Gudang, Johor, and to examine the relationship between these factors and purchasing decisions. A quantitative approach was adopted, involving the distribution of 100 randomly selected questionnaires in the study area. Findings reveal that while location was ranked as the most influential factor in the selection process, the surrounding environment and neighbourhood emerged as the most significant determinant in actual purchase decisions. Conversely, socio-cultural factors and location were found to be statistically insignificant in influencing purchase decisions. This may be attributed to the fact that respondents had already purchased sub-sale properties in Pasir Gudang, rendering location a non-variable. Overall, the study concludes that socio-cultural factors have minimal impact compared to other considerations when buying sub-sale homes.